Utilization of Siwalan Waste (Borassus flabellifer L.) as a Prototype of Active Carbon-Based Batteries Using Brunauer Emmett Teller (BET) and Analysis of Variance (ANOVA) Method - Nugraha, Isna; Anshori, Husna Zaka; Arier, Tivani Nava; Aliya, Izra Noor; Ningrum, Dwi Mulyati; Gufron, Achmad (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Currently, electricity use in Indonesia has soared and continues to increase every year. New renewable energy will be the main alternative for the country as a source of electricity. Alternative energy sources can come from biomass such as Siwalan shell waste. This waste has a composition of 18.52% hemicellulose, 11.90% cellulose, 0.23% lignin, 0.1% nitrogen, 13.80% water, 4.46% ash, 44.58% carbon and 6.41% volatile matter. % which is the chemical component of the basic ingredient for making activated carbon. Thus, the aim of this research is to determine the capacitance of a battery prototype from activated carbon from Siwalan shell waste. The method used is a quantitative method by taking data from the results of the Brunauer Emmett Teller test and the Cyclic Voltammetry test. Carbon is activated using KOH with varying concentrations of 1 M; 1.5 M; 2M; 2.5 M. The results of the surface area of activated carbon in the BET test were 13,636 m2/g; 20,941 m2/g; 28,191 m2/g; and 29,871 m2/g and in manual calculations using the BET method it was obtained 13,647 m2/g; 20,950 m2/g; 28,197 m2/g; and 29,875 m2/g. From testing and manual calculations, Siwalan shell carbon at a KOH concentration of 2.5 M has the largest surface area and has the potential to be the best active carbon material for making battery prototypes.